Penerapan Sistem Absensi Siswa Menggunakan Teknologi Internet Of Things - Baiq Andriska Candra Permana; Muhammad Djamaluddin; Suhro Wahyudi Saputra (Infotek: Jurnal Informatika dan Teknologi, 2023)
One important factor to determine the discipline of a student is to record the student's attendance. The attendance system that has been used so far is to call the student's name and then record their attendance on paper, this manual technique causes various problems,for example it takes a long time to record data,the attendance archive is damaged due to tearing and various other conditions. In addition,the attendance system that has been running so far has not been able to accurately record student attendance, such as student arrivals on time or not. Radio Frequency Identification (RFID) based on NodeMcu ESP8266 works with the internet network to overcome problems that have occurred so far. With this attendance system not only facilitates the attendance process but also assists teachers in recording student attendance. The system device works accurately with a maximum card scan distance of 4cm with a perfect accuracy level